Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

1. Which of the following expressions is equivalent to 3 + 3×12 ÷ 4×3?

6×12÷4×3

3 + 3×12÷12

3+3×3×3

3÷36÷4×3​


Sagot :

To find which one is equivalent to 3+3*12/4*3, we need to first evaluate and then compare to other expressions to find which one is equivalent to the expression. Using PEMDAS, we first do the multiplication and division, and then do addition.
3+3*12/4*3 = 3+36/4*3 = 3+9*3 = 3+27 = 30
Now that we know what the expression equals to, we can evaluate other equations until we find the same answer.
6*12/4*3=72/4*3=18*3=48
3+3*12/12=3+3*1=3+3=6
3+3*3*3= 3+27*3=3+81=84
3/36/4*3=9/36/4= 1/4/4 = 1/4*1/4 = 1/16
None of them are equivalent
Hope this helps
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.